Evaluation of the Effectiveness of National Tax Collection Performance - Khoirul Bahriyah (Business Finence Analyst Co.,, 2025)
The purpose of this study is to evaluate the effectiveness of national tax collection for the period 2022-2024. The background of this research relates to tax revenue, which plays a vital role as the primary source of state financing, and the challenges faced in achieving the effectiveness of national tax revenue targets. Using a descriptive quantitative method, the evaluation analyzes the ratio of realization effectiveness against tax revenue targets, as well as the factors influencing performance in state revenue collection. Secondary data were utilized from the Directorate General of Taxes (DGT) and the Central Statistics Agency (BPS). The results show that the highest effectiveness occurred in 2022 (115.61%), driven by economic recovery post-pandemic and high global commodity prices. Meanwhile, effectiveness declined in 2023 to 102.73% and in 2024 to 99.66%, due to weakening commodity prices, global uncertainties, and declining domestic consumption. Although nominal achievements increased, fiscal effectiveness requires continued strategies focusing on expanding the tax base, digitizing supervision, and improving tax incentive policies. These findings can provide input for fiscal authorities in strengthening a sustainable state revenue structure. Keywords: tax effectiveness ; state revenue ; collection ; realization ; DGT ; fiscal policy.